Analysis of Customer-Based Brand Equity Strategy Through The Digital Branding Process in The Social Sharing Happiness Campaign As A Social Crowdfunding Startup - Puti Halimah; Uud Wahyudin; Trie Damayanti (Eduvest - Journal of Universal Studies, 2025)
This study examines the influence of consumer-based brand equity through the digital branding process on consumer loyalty in the Sharing Happiness social campaign. With the increase in internet users in Indonesia, people's behavior in donating has also undergone a transformation, switching to digital platforms. This study uses a quantitative method with a correlational approach to analyze the relationship between brand equity and consumer loyalty, which is measured through repeat purchase, retention, and referral. The results of the analysis show that high brand equity has a positive impact on consumer loyalty. Simultaneous and partial hypothesis tests show that the Customer Based Brand Equity strategy significantly affects consumer loyalty in the form of repeat donations, positive comments, and referrals. This research provides insights for business people and marketers about the importance of branding strategies in the digital era to increase consumer loyalty in the crowdfunding sector. This finding is expected to be a reference for the development of adaptive and innovative marketing communication strategies in the face of dynamic changes in consumer behavior.